Associação de eventos adversos cardiovasculares e o uso de agentes antipsicóticos em pacientes esquizofrênicos: revisão sistemática de estudos observacionais - Silva, Ana Amancio Santos da (2016)
There are controversies about the association of cardiovascular adverse events and the use of antipsychotic agents in schizophrenia patients. Cardiovascular diseases are responsible for the main causes of mortality in the world. And it has been observed high mortality rates in patients with schizophrenia. Thus, the objective of this research was to determine whether there is an association between the risk of cardiovascular adverse events and the use of antipsychotic agents in schizophrenia patients. Were surveyed on LILACS from 1982 to November 2015, PUBMED (public version of MEDLINE) de1962 to November 2015, The Cochrane Controlled Clinical Trials Database (CENTRAL) 2015 volume 10 and PsycINFO until November 2015. Two reviewers selected and accessed from independently observational studies reporting associations between cardiovascular adverse events and the use of antipsychotic agents. Three observational cohort items were included to assess quality. The quality of the articles was assessed using the Newcastle-Ottawa Scale, in which two articles received three stars and an article won four stars, indicating high risk of bias. Clinical heterogeneity was evident and there is no meta-analysis. Data best quality articles were used to estimate preliminary results. This systematic review shows a preliminary result of the variables: arrhythmia and mortality. When analyzed arrhythmia demonstrated that there was a significant increase in patients with schizophrenia which makes use of antipsychotic agents with compared to people without psychotic diagnosis. Mortality from cardiovascular disease, demonstrating a significant increase in the group of participants who received antipsychotics and schizophrenia were compared to the general population not taking antipsychotics. The evidence found so far were insufficient to demonstrate or rule out the existence of the association between the use of neuroleptic drugs for the treatment of patients with schizophrenia and adverse cardiovascular events.